Elimination of Chaotic Ferroresonant Oscillations Originated from TCSC in the Capacitor Voltage Transformer. Issue 3 (4th May 2018) - Abbasi, Ataollah; Fathi, Seyed Hamid; Mihankhah, Amin
ABSTRACT: Ferroresonance is one of the complex phenomena, which occurs in power network. This can create thermal and insulation problems in the power system equipments. It can also cause chaotic oscillations in the power network. The magnitude of the power system capacitor is one of the important factors that lead to ferroresonance in capacitor voltage transformers (CVTs). Thyristor controlled series capacitors (TCSCs) are applied for series compensation in the transmission line of power system. In normal operation, these equipments have capacitance magnitude up to three times of fixed capacitor such that the increased value of transmission line capacitor, which is one of the reasons for ferroresonance occurrence, is provided. This paper studies and investigates the effects of TCSCs on the ferroresonance in the CVTs. Because of nonlinear dynamics of ferroresonance, bifurcation theory is utilized in this paper. Using this theory, variation of system parameters that cause chaotic ferroresonant oscillations can be efficiently analyzed. By using bifurcation and phase plane diagrams, behavioral variations of the system with TCSC can be easily reviewed in this case. The results show that TCSCs raise ferroresonance occurrence in CVT. Since thermal and insulation problems may happen during the occurrence of ferroresonance in CVT and TCSC, a device is used to limit and remove these chaotic oscillations; literally called ferroresonance limiter. Obtained results strongly and efficiently show effectiveness of using this method for restricting ferroresonant oscillations.